Seismic Performance Analysis of CFST Stiff Skeleton Concrete Arch Bridge considering Non-planar Sectional Stress Induced by Balanced Ring-casting Construction. Issue 1 (2nd January 2023) - Zhao, Canhui; Duan, Jiahong; Tang, Cheng; Deng, Kailai; Shang, Congjin; Zhang, Xiaoyu
ABSTRACT: Concrete-filled steel tube (CFST) stiff skeleton concrete arch bridges can be designed with longer spans using balanced ring-casting construction. However, this construction method induces non-planar sectional stress in the arch rings. To investigate the influence of the non-planar sectional stress on the seismic performance of arch bridges, we developed two numerical models of a typical arch bridge. The first model simulates the construction process of balanced ring-casting, while the second model ignores the construction process. The dynamic analysis results reveal that, if the construction process is ignored, the seismic risks of concrete cracking and reinforcement yielding in the arch rings will be underestimated.